Meet the Expert : John Chapin & Mike Roberts on Real-World Performance Practices for AWS Lambda - Chapin, John; Roberts, Mike (O'Reilly Media, Inc., 2020)
Join us for this edition of Meet the Expert with Mike Roberts and John Chapin from Symphonia to learn how to build high performance, Java-based, serverless applications using AWS Lambda. Mike and John will describe some great use-cases for Lambda, distill the concerns of cold starts (with data!), and dive into some recommended practices you can use in your own work. O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions. What you'll learn and how you can apply it By the end of this live show, you'll better understand: What types of real-world applications people are building with AWS Lambda, and whether Lambda is a good fit for your products What "Cold Starts" are in Lambda, why people worry about them, and what impact they actually have on performance, based on various application criteria Recommended practices for architecting, building, and deploying Java-based Lambda functions that optimize the runtime speed of your functions, while still having an eye towards costs and without introducing unnecessary developer burden